1996
DOI: 10.1177/0887302x9601400111
|View full text |Cite
|
Sign up to set email alerts
|

Key Dimensions of Women's Ready-to-Wear Apparel: Developing a Consumer Size-Labeling System

Abstract: Key dimensions were selected for women's ready-to-wear garments to generate an anthropometric sizelabeling system designating garment size with body measurements. Two different statistical analyses were used to select key dimensions: residual variance analysis and factor analysis. The results of the study show that (a) the key dimensions selected by both means of analysis are similar, (b) the key dimensions used in most mail-order catalogs are appropriate, and (c) in addition to the key dimensions currently in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 10 publications
0
30
0
Order By: Relevance
“…There is an urgent need to alert consumers that the crotch length affects the waistband measurements as pants that have a longer crotch tend to have a smaller waistband closer to the natural waistline of an individual. This can assist consumers in understanding fit issues in order to formulate consumer-friendly ways of selecting garments for acceptable fit (Chun-Yoon and Jasper 1996). Figure types affect the sizing measurements used in the manufacture of apparel.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an urgent need to alert consumers that the crotch length affects the waistband measurements as pants that have a longer crotch tend to have a smaller waistband closer to the natural waistline of an individual. This can assist consumers in understanding fit issues in order to formulate consumer-friendly ways of selecting garments for acceptable fit (Chun-Yoon and Jasper 1996). Figure types affect the sizing measurements used in the manufacture of apparel.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Zwane consumers prefer the most informative size description system that indicates body measurements. In a separate study, Chun-Yoon and Jasper (1996) used key dimensions, the hip and waist circumferences and crotch height for women's garments in order to develop a size-labelling system that designates garment size with body measurements. They found that these key dimensions were appropriate but another key dimension representing length or height was needed for more accuracy.…”
Section: Purpose and Objectives Of The Studymentioning
confidence: 99%
“…Process the data using fitting techniques, such as B-spline curves, to smooth and connect points of a crosssection at one landmark or a space curve between two landmarks. 3 . Compute the measurements such as circumference, distance, angle, etc.…”
Section: D Body Measurementmentioning
confidence: 95%
“…In the period 1970-2010, statistical methods, such as principal component and factor analysis, correlation, multiple regression and discriminate analysis, were applied to large sets of data (Chun-Yoon and Jasper, 1996;Green, 1981;Hsu, 2009;Jung et al , 2010;Laing et al , 1999;Robinette, 1986;Salusso-Deonier, 1985). The general approach can be summarised as selecting the body site or segment of interest (e.g.…”
Section: Development Of Sizing Systems From Anthropometric Datamentioning
confidence: 99%